New Violence Against Women - Femenías, María Luisa (Nomadías, 2009)
Violence against women is multiple. Recently, “domestic violence” has increased specially among middle class and high middle class. This short article intends to analyze a cluster of causes related to globalization and man selfrespect as “breadwinner” and head of the family. We learn of this kind in comparison to physical, moral, psychic and linguistic violence.